Pulmonary system limitations to endurance exercise performance in humans - Amann, M. (Experimental Physiology, 2012)
Accumulating evidence over the past 25 years depicts the healthy pulmonary system as a limiting factor of whole body endurance exercise performance. This brief overview emphasizes three respiratory system-related mechanisms which impair O2 transport to the locomotor musculature [arterial O2 content (CaO2) x leg blood flow (QL)], i.e. the key determinant of an individual's aerobic capacity and ability to resist fatigue. First, the respiratory system often fails to prevent arterial desaturation substantially below resting values and thus compromises CaO2. Especially susceptible to this threat to convective O2 transport are well-trained endurance athletes characterized by high metabolic and ventilatory demands and, likely due to anatomical and morphologic gender differences, active females. Second, fatiguing respiratory muscle work (Wresp) associated with strenuous exercise elicits sympathetically-mediated vasoconstriction in limb-muscle vasculature which compromises QL. This impact on limb O2 transport is independent of fitness level and affects all individuals, however, only during sustained, high-intensity endurance exercise performed above ~85% VO2max. And third, excessive fluctuations in intrathoracic pressures accompanying Wresp can limit cardiac output and therefore QL. Exposure to altitude exacerbates the respiratory system limitations observed at sea level and further reduces CaO2 and substantially increases exercise-induced Wresp. Taken together, the intact pulmonary system of healthy endurance athletes impairs locomotor muscle O2 transport during strenuous exercise by failing to ensure optimal arterial oxygenation and compromising QL. This respiratory system-related impact exacerbates the exercise-induced development of fatigue and compromises endurance performance.